Laboratory exposure to Coccidioides: lessons learnt in a non-endemic country. Issue 4 (August 2019) - Porte, L.; Valdivieso, F.; Wilmes, D.; Gaete, P.; Díaz, M.C.; Thompson, L.; Munita, J.M.; Alliende, R.; Varela, C.; Rickerts, V.; Weitzel, T.
Summary: Coccidioides is a primary pathogenic fungus, which infects humans through highly infectious arthroconidia, causing substantial morbidity including life-threatening disseminated infections. Due to the low infectious dose, laboratory personnel might become infected during diagnostic procedures. Accordingly, coccidioidomycosis is reported as the most frequent laboratory-acquired systemic mycosis worldwide. This risk is aggravated in non-endemic countries, where the diagnosis may not be suspected. We report on an inadvertent exposure of 44 persons to Coccidioides posadasii in a clinical microbiology laboratory in Chile, the measures of containment after rapid diagnosis with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, and the lessons learnt in a non-endemic setting.